Smart paint sensor for monitoring structural vibrations - Al-Saffar, Y; Aldraihem, O; Baz, A (Smart materials and structures, 2012)
A class of smart paint sensors is proposed for monitoring the structural vibration of beams. The sensor is manufactured from an epoxy resin which is mixed with carbon black nano-particles to make it electrically conducting and sensitive to mechanical vibrations. A comprehensive theoretical and experimental investigation is presented to understand the underlying phenomena governing the operation of this class of paint sensors and evaluate its performance characteristics. A theoretical model is presented to model the electromechanical behavior of the sensor system using molecular theory. The model is integrated with an amplifier circuit in order to predict the current and voltage developed by the paint sensor when subjected to loading. Furthermore, the sensor/amplifier circuit models are coupled with a finite element model of a base beam to which the sensor is bonded. The resulting multi-field model is utilized to predict the behavior of both the sensor and the beam when subjected to a wide variety of vibration excitations. The predictions of the multi-field finite element model are validated experimentally and the behavior of the sensor is evaluated both in the time and the frequency domains. The performance of the sensor is compared with the performance of conventional strain gages to emphasize its potential and merits. The presented techniques are currently being extended to sensors that can monitor the vibration and structural power flow of two-dimensional structures.